2014
DOI: 10.1214/14-aoas748
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal high-dimensional principal components analysis with application to diffusion tensor imaging of multiple sclerosis

Abstract: We develop a flexible framework for modeling high-dimensional imaging data observed longitudinally. The approach decomposes the observed variability of repeatedly measured high-dimensional observations into three additive components: a subject-specific imaging random intercept that quantifies the cross-sectional variability, a subject-specific imaging slope that quantifies the dynamic irreversible deformation over multiple realizations, and a subject-visit specific imaging deviation that quantifies exchangeabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…In fact, it is possible that registering the 2D representation is preferable to whole brain registration a priori in certain applications. Note also that MFPCA (Di et al 2009) and LFPCA (Zipunnikov et al 2011; Zipunnikov et al 2014), methods have been shown to isolate registration error as a part of the model (Lee et al 2015), thus raising the intriguing possibility of DTI processing streams that dramatically decrease the need and importance of whole brain template-based registration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is possible that registering the 2D representation is preferable to whole brain registration a priori in certain applications. Note also that MFPCA (Di et al 2009) and LFPCA (Zipunnikov et al 2011; Zipunnikov et al 2014), methods have been shown to isolate registration error as a part of the model (Lee et al 2015), thus raising the intriguing possibility of DTI processing streams that dramatically decrease the need and importance of whole brain template-based registration.…”
Section: Discussionmentioning
confidence: 99%
“…[11,[36][37][38] There has been also studies about the relationship between CC involvement's patterns and prognosis of MS. [7][8][9][10][11] Most of them showed that the damage to white matter network especially CC contributes to the reduced processing speed in task specific abilities. [39] A significant increase in CC's MD was observed in relapsing remitting MS, even in benign form. [40][41][42][43][44] Moreover, patterns of tract FA reduction for cognitive test, including localization of lesions in the body and splenium of the CC, only partially overlapped with T2 lesions, supporting that NAWM abnormality contributes to cognitive dysfunction.…”
Section: As a Prognosis Indicatormentioning
confidence: 94%
“…On the other hand, in normal appearing brain tissue, CC's FA and axial diffusivity demonstrated further decline over time, while no significant change in radial diffusivity was observed. [47] Hence, the decline in axial diffusivity may suggest involvement of axonal loss and degeneration in normal appearing brain tissue at the early stage before active lesions develop, possibly attributing to poorer prognosis and progressive disability often observed in MS patients despite treatment. Many recent studies agree on the fact that longitudinal changes are most rapid in CC area of the brain in MS disorder in different types of imaging.…”
Section: As a Prognosis Indicatormentioning
confidence: 99%
“…It should be noted that the estimation procedures used in [6, 17, 21] are not directly applicable here due to the nonlinear association map in (1). …”
Section: Methodsmentioning
confidence: 99%
“…Many parametric mixed effects models including both fixed and random effects are the predominant approach for characterizing both the temporal correlations and random individual variations. Although there is a great interest in the analysis of functional data with various levels of hierarchical structures [11, 18, 7], only a handful of them [6, 17, 21] focused on the development of linear mixed models for longitudinal image data. Recently, there was some attempt on the development of hierarchical geodesic models on diffeomorphism for longitudinal shape analysis [15].…”
Section: Introductionmentioning
confidence: 99%